Lupus Nephritis with Thymoma Managed by Thoracoscopic Surgery and Prednisolone - Iijima, Takashi (Intern Med, 2017)
A 48-year-old woman was admitted to our hospital to undergo evaluation for fatigue, severe weight loss, and nephrotic range proteinuria. Light microscopy of a renal biopsy specimen revealed class III (A) lupus nephritis, while immunofluorescence and electron microscopy only showed sparse immune deposits with findings that were not typical of lupus nephritis. Computed tomography revealed a mass in the anterior mediastinum, which was resected. The examination of the surgical specimen revealed type A noninvasive thymoma. In combination with thymomectomy, postoperative steroid therapy achieved the prompt remission of lupus nephritis. In this patient, thymoma-related autoimmunity may have contributed to the exacerbation of lupus nephritis.